Municipal Development. ACORDAR in alliance with local governments to develop territories - Flores Medina, Ronald C.; Vázquez Vasquez, Augusto C.; López Fonseca, Ernesto Antonio; Acuña Acuña, Ever M.; Rodríguez, Naví; Centeno Sánchez, José Augusto; Monge Zamora, Marvin Antonio; Centeno Zamora, Janira Damarys (Catholic Relief Services, 2012)
This publication is the result of a participatory experience capitalization, facilitated by the International Center for Tropical Agriculture for the project “Alliance to Create Opportunities for Rural Development through Agro-enterprise Relationships” (ACORDAR). The experiences compiled are the following: "Producer Organizations in Alliance with Municipal Governments to Strengthen Value Chains" and "Linking Actors to Contribute to the Economic and Social Development of the Nicaraguan Municipality of Rancho Grande."